Exploring network selection techniques for multicast groups in heterogeneous wireless environments. Issue 1 (2014) - ,; ,; ,
Abstract : Purpose – Coexistence of various wireless access networks and the ability of mobile terminals to switch between them make an optimal selection of serving networks for multicast groups a challenging problem. Since optimal network selection requires large dimensions of data to be collected from several network locations and sent between several network components, the scalability can easily become a bottleneck in large‐scale systems. Therefore, reducing data exchange within heterogeneous wireless networks is important. The paper aims to discuss these issues.Design/methodology/approach – The authors study the decision‐making process and the data that need to be sent between different network components. To analyze the operation of the wireless heterogeneous network, the authors built a mathematical model of the network. The objective is defined as a minimization of multicast streams in the system. To evaluate the heuristic solutions, the authors define the upper and lower bounds to their operation.Findings – The proposed heuristic solutions substantially reduce the usage of bandwidth in mobile networks and exchange of information between the network components.Originality/value – The authors proposed the approach that allows network selection in a decentralized manner with only limited information shared among the decision makers. The authors studied how different sets of information available to decision makers influenced the performance of the system. The work also investigates the usage of multiple paths for multicast in heterogeneous mobile environments. Acknowledgements : The work described in this paper has been conducted as a part of the ADIMUS (Adaptive Internet Multimedia Streaming) project, which is funded by the NORDUnet‐3 programme. The authors wish to thank Trenton Schulz and Bjarte Østvold for discussions during the preparation of this paper.